Penerapan Teori PembelajaranKognitif Menggunakan Film untuk Meningkatkan Pemahaman Mahasiswa - Patty, Elyakim; Suendra, Elfina Malya; wadihar, Muhammad Nur wazda; Ahmad, Lalu Daffa Al; Nabila, Rizki; Madazzaman, Mukti (Universitas Bumigora, 2025)
Cognitive learning theory emphasizes the importance of individuals being able to understand, connect, and apply concepts in various situations. However, in practice, these concepts are often difficult for students to grasp. This study aims to explore the application of cognitive learning theory through film as a medium to enhance students’ understanding. The Imitation Game was used as the main medium to illustrate cognitive and collaborative problem-solving processes. The study used a qualitative case study approach, involving first-semester students enrolled in the Learning and Instruction Theory course. Data were collected through participatory observation during the film screening, structured group discussions, and semi-structured interviews conducted before and after the viewing. The results of this study showed an increase in students’ ability to relate scenes from the film to cognitive learning concepts such as analytical thinking, cognitive schemas, and teamwork, as described by Piaget and Vygotsky. The use of film was found to concretize abstract concepts, promote active engagement, and strengthen students’ critical reflection on the real-life application of theory. Films that present complex problem-solving scenarios also stimulate students’ critical and collaborative thinking more effectively than conventional teaching methods. This study concludes that film is an innovative strategy in teaching learning theories, providing visual experiences that enhance conceptual understanding and